2009
DOI: 10.1111/j.1365-2923.2008.03248.x
|View full text |Cite
|
Sign up to set email alerts
|

Student perceptions of medico-legal autopsy demonstrations in a student-centred curriculum

Abstract: OBJECTIVES Teaching autopsies in undergraduate medicine, although traditionally considered valuable by both educators and students, have been marginalised in modern curricula. This study explored medical students' experiences of the medico-legal autopsy demonstrations which formed part of their training in forensic medicine. METHODSIn this phenomenological study, qualitative data obtained by interviewing 10 Year 4 medical students from various sociocultural backgrounds were interpretively examined. One-to-one,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 14 publications
4
47
0
Order By: Relevance
“…Our results point to a hidden curriculum in such laboratories, one that transforms attitudes and transmits values to students both by what is (and what is not) taught and how such teaching features in the curriculum (Burton, 2003). In one study about medico-legal autopsy teaching, autopsies were found to carry a considerable hidden curriculum concerning attitudes of respect, empathy, and compassion (McNamee et al, 2009). Laboratories promote reflection (Lachman and Pawlina, 2006) and develop students' humanity.…”
Section: Ambivalent Emotionmentioning
confidence: 74%
See 1 more Smart Citation
“…Our results point to a hidden curriculum in such laboratories, one that transforms attitudes and transmits values to students both by what is (and what is not) taught and how such teaching features in the curriculum (Burton, 2003). In one study about medico-legal autopsy teaching, autopsies were found to carry a considerable hidden curriculum concerning attitudes of respect, empathy, and compassion (McNamee et al, 2009). Laboratories promote reflection (Lachman and Pawlina, 2006) and develop students' humanity.…”
Section: Ambivalent Emotionmentioning
confidence: 74%
“…A phenomenological study of medical students, in contrast, found that future physicians felt it important for all medical practitioners to attend at least one autopsy in the course of their professional training (McNamee et al, 2009). Physical therapy and medical students may have different opinions on this subject because, compared to medical doctors, physical therapists seldom deal with human death in clinical practice.…”
Section: Ambivalent Emotionmentioning
confidence: 99%
“…At the same time, very few studies have addressed the effects of confronting students with dead bodies and most of these studies have focused on autopsies [6][7][8] as well as course content. In addition, these studies did not cover undergraduate but mainly postgraduate education [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…A second reason could be that the SWOT analysis might not have been the best tool with which to evaluate the perceptions of students. The study also reiterated the findings of McNamee et al [12] regarding the emotional aspect surrounding the attendance of forensic autopsies, indicating that the autopsy aided in the description of trauma and differentiated between natural and unnatural causes of death.…”
Section: Discussionmentioning
confidence: 65%
“…In a study by McNamee et al, [12] from the Department of Forensic Medicine, Nelson R Mandela School of Medicine, University of KwaZulu-Natal, Durban, 10 students took part in semistructured interviews after completion of the forensic medicine practical rotation. All students experienced a degree of discomfort, 70% indicated that they had a better understanding of the mechanism of death and could better differentiate between natural and unnatural causes of death, and 80% indicated that the description of trauma aided a great deal.…”
mentioning
confidence: 99%